New adaptive reclosing technique using second-order difference of THD in distribution system with BESS used as uninterruptible power supply. (September 2017) - Seo, Hun-Chul
Highlights: The transient phenomena of BESS at fault conditions are analysed. The adaptive reclosing technique in the distribution system with BESS is proposed. The proposed technique is verified by simulating the various fault conditions. The superiority of proposed technique is proved by comparing with conventional reclosing method. Abstract: This paper proposes a new adaptive reclosing technique that considers the battery energy storage system (BESS) in a distribution system. The proposed technique focuses on operation of the BESS as an uninterruptible power supply (UPS). The algorithm detects the fault clearance using second-order differences of total harmonic distortion (THD) (SODT) of the current supplied by the BESS and allows the BESS to keep feeding to the healthy phase. A synchronism check is adopted between the utility and the BESS to minimize the transients at the moment of reclosing. To verify the proposed algorithm, the whole system and algorithm were modeled using ATP-EMTP. Various simulations are performed by varying the fault clearance time, fault types, fault resistances, and fault locations. The simulation results show that the BESS can be operated as a UPS and provide an improved reclosing scheme.